2016
DOI: 10.1177/2165143415588047
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Post-School Success

Abstract: The purpose of this systematic review was to (a) systematically review the literature to identify National Longitudinal Transition Study-2 secondary analyses articles published since 2009 that met the quality indicators for correlational research, (b) further extend the findings of Test et al. by identifying additional evidence to support the existing in-school predictors of post-school success, and (c) identify any new in-school predictors of post-school success for youth with disabilities. Based on the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 21 publications
2
116
1
Order By: Relevance
“…Data analysis coding. We analyzed the final 22 studies to identify (a) predictors that build on findings from and Mazzotti et al (2016) and (b) new predictors of postschool success. We coded the 22 studies for content, which also included recording effect sizes for each study variable.…”
Section: Selection Procedures Inclusion/exclusion Criteriamentioning
confidence: 99%
“…Data analysis coding. We analyzed the final 22 studies to identify (a) predictors that build on findings from and Mazzotti et al (2016) and (b) new predictors of postschool success. We coded the 22 studies for content, which also included recording effect sizes for each study variable.…”
Section: Selection Procedures Inclusion/exclusion Criteriamentioning
confidence: 99%
“…To gain work-based social skills in high school, students with disabilities should be provided opportunities to participate in WBLEs. Paid and unpaid work experiences in high school have been identified as one of the strongest predictors of post-school employment, education, and independent living for youth with disabilities (Mazzotti et al, 2016(Mazzotti et al, , 2020. These work experiences may include job shadowing, work sampling, service learning, internships, and/or apprenticeships (Cease-Cook et al, 2015;Luecking & Luecking, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An innovative component to the Nittrouer et al intervention was the addition of a self-determination intervention (i.e., goal-setting, self-management) to address work-based problem behaviors. There is a plethora of research that indicates involving students in the goalsetting and self-management process can increase self-determination, self-advocacy, and potentially post-school employment outcomes (Mazzotti et al, 2016(Mazzotti et al, , 2020Wehmeyer et al, 2013). Inclusion of a self-determination component in the Nittrouer et al study provides evidence that involving students in the FBA process and teaching students to selfset goals and manage their behavior on the job may be a beneficial intervention for reducing problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Earning a college degree is increasingly important to a person's long-term success (Carnevale et al, 2016), yet young adults with disabilities are less likely to attend and complete postsecondary education than their peers (Newman et al, 2011). In a sustained effort to understand how best to support students with disabilities in pursuing postsecondary programs of study, prior research has (a) identified high school factors correlated with college participation (Mazzotti et al, 2015;Test et al, 2009) and (b) described postsecondary experiences that support college participation and persistence within this population (Dukes et al, 2017;Kutscher & Tuckwiller, 2019). Despite these efforts, researchers have yet to understand what reliably "works" for students with disabilities (Dukes et al, 2017;Haber et al, 2016), and individuals with disabilities continue to experience inequitable outcomes after high school.…”
mentioning
confidence: 99%